Intensity of cercospora leaf spot of mothbean (Vigna aconitifolia) in major growing areas of Rajasthan - Santosh Kumari; Data Ram Kumhar; Jasveer Singh; Shipra Sharma; B.D.S. Nathawat (Annals of Agricultural Research, 2025)
A comprehensive survey was undertaken across key Mothbean cultivation regions in Rajasthan during Kharif season 2023 and 2024, revealing a pressing concern: the prevalence of Cercospora leaf spot disease attributed to Cercospora canescens. This fungal affliction significantly impacts agricultural productivity, notably in Bikaner, Sri Ganganagar, Churu and Barmer districts. The survey findings indicated an average disease intensity of 27.76% across the surveyed districts of Rajasthan. Notably, Sri Ganganagar exhibited the highest average disease intensity at 31.85%, closely followed by Bikaner at 29.67%, and Churu 26.51% with Barmer registering the lowest at 23.03%.